Insight Report: “Innovative, automated use of real-world healthcare data to improve outcomes for patients with ovarian cancer” project online public involvement session - Piggin,M; Johnson,H; Baker,K; Nkolobe,B; Glampson,B; Samani,A; Tookman,L (2022)
A summary of the insights gathered from a public involvement discussion involving patients and cares with lived experience of ovarian cancer and their views on a health data project “Innovative, automated use of real-world healthcare data to improve outcomes for patients with ovarian cancer”